The influence of secondary schooling on the subjectivity about themselves of young people who fail in it. - Redondo, Jesus M. (Revista de Psicología, 1999)
An analysis is presented, of data of the diverse aspects of the self-percepcion that adolescents have in the beginning and end of their high school period, at the ages of 14 though 16 years, in a sample from the Vasco Country. These analysis allows us to sustain that the extension of the school period with the current academic design harms the youngpeople that fail in school, especially in aspects of subjectivity related to themselves as students. This disadventage transforms personal differences into social inequilities accepted by themselves as result of the school process.